Constitutional-legal institution for the protection of the state in the Republic of Belarus - Ignatenko, Andrey S. (Journal of the Belarusian State University. Law, 2023)
The object of research is social relations connected with the defense of the Republic of Belarus. The author’s vision of the concept of protection of the Republic of Belarus, as well as the classification of public relations in the field of protection of the Republic of Belarus, which are the subject of constitutional and legal regulation, is proposed. The article reflects theoretical and legal approaches to the formation of a constitutional and legal institution for the protection of the Republic of Belarus.